Descriptive And Theoretical Approaches To African Linguistics - Sibanda, Galen; Ngonyani, Deo; Choti, Jonathan; Biersteker, Ann (My University, 2022)
Descriptive and theoretical approaches to African Linguistics contains a selection of revised and peer-reviewed papers from the 49th Annual Conference on African Linguistics, held at Michigan State University in 2018. The contributions from both students and more senior scholars, based in North America, Africa and other parts of the world, provide a glimpse of the breadth and quality of current research in African linguistics from both descriptive and theoretical perspectives. Fields of interest range from phonetics, phonology, morphology, syntax, semantics to sociolinguistics, historical linguistics, discourse analysis, language documentation, computational linguistics and beyond. The articles reflect both the typological and genetic diversity of languages in Africa and the wide range of research areas covered by presenters at ACAL conferences.
Keywords: African linguistics; language varieties; phonological constraints